Association between standard base excess and acute kidney injury in intensive care unit patients: a study based on the medical information mart for intensive care database - Dongfang Yang; Weiguang Zhang; Ying Cao; Yan Zhang; Changlin Yin (BMC Nephrology)
Abstract Background This study was to analyze the association between standard base excess (SBE) and the risk of acute kidney injury (AKI) in intensive care unit (ICU) patients. Methods In this retrospective cohort study, data were collected from the Medical information mart for intensive care (MIMIC)-IV database between 2008 and 2019. SBE was categorized based on tertiles. The outcome was whether AKI occurred 24 h after admission to ICU. Univariate and multivariate logistic regression models were utilized to evaluate the association between SBE and the risk of developing AKI. Subgroup analyses were conducted based on age, sex, cardiogenic shock, sepsis, and scores. Results Within the median follow-up of 1.690 (1.245, 2.576) days, 4,499 (40.7%) cases of AKI were identified. Lower (OR: 1.11, 95% CI: 1.00-1.22, P = 0.048) or higher (OR: 1.14, 95% CI: 1.04-1.26, P = 0.008) levels of SBE were associated with a higher risk of developing AKI. In our subgroup analysis of patients aged < 70 years, higher or lower SBE were associated with a higher risk of AKI. Among patients not suffering from cardiogenic shock, both higher and lower SBE values were associated with an increased risk of AKI. In the absence of sepsis, elevated SBE was correlated with an increased risk of AKI. In patients with a qSOFA ≥ 2, both higher and lower SBE values were associated with an increased risk of developing AKI. For patients with a CCI ≥ 2, elevated SBE was found to be correlated with an increased risk of AKI. In the female subgroup, elevated SBE was associated with an increased risk of developing AKI; whereas, in the male subgroup, reduced SBE was correlated with a higher risk of AKI. Conclusion Both excessively high and low levels of SBE are associated with an increased risk of AKI in ICU patients. Therefore, it may be crucial for ICU patients to monitor SBE levels and promptly correct any abnormalities in acid-base balance to reduce the risk of developing AKI. Clinical trial number Not applicable.